Evaluating the UV-C sensitivity of Coxiella burnetii in skim milk using a bench-scale collimated beam system and comparative thermal sensitivity study by high-temperature short-time pasteurization - Pendyala, Brahmaiah; Vashisht, Pranav; Chen, Fur-Chi; Sanchez, Savannah E.; Comstock, Bob; Omsland, Anders; Patras, Ankit (Frontiers in Food Science and Technology, 2023)
Introduction:Coxiella burnetii is a zoonotic Gram-negative obligate intracellular bacterial pathogen and the causative agent of query (Q) fever in humans. Contamination of milk by C. burnetii, as a consequence of livestock infection, is a significant public health concern. Effective methods to inactivate C. burnetii in milk are a critical aspect of food safety. Implementation of non-thermal UV-C processing technologies in the dairy industry can effectively preserve the sensory and nutritional quality of raw milk products while ensuring their safety, making them a viable alternative to traditional high-temperature short-time (HTST) pasteurization methods. Methods: Optical light attenuation factors, such as the absorption, scattering, and reflection by skim milk (SM) were evaluated using a spectrophotometer. SM inoculated with an avirulent strain of C. burnetii was irradiated using a collimated beam device equipped with a low-pressure UV-C 254 nm lamp at doses from 0 to 12 mJ/cm2. Optical properties were considered for the evaluation of the delivered UV-C dose. The pasteurization treatment was conducted using a lab scale HTST pasteurizer (72°C/15 s). The verification studies were conducted using Escherichia coli ATCC 25922 inoculated in a phosphate buffer (transparent fluid) and humic acid (opaque fluid). Salmonella enterica serovar Muenchen ATCC BAA 1674 inoculated in SM was tested for its suitability as a surrogate for C. burnetii, a bacterium that requires specialized equipment and expertise for experimentation. Results and Discussion: Absorption, reduced scattering coefficient, and the reflectance of SM at 254 nm were measured as 19 ± 0.3/cm, 26 ± 0.5/cm, and 10.6%, respectively. The UV-C results showed a log-linear inactivation of C. burnetii in SM with the UV-C sensitivity (D10) value of 4.1 ± 0.04 mJ/cm2. The results of HTST pasteurization revealed that C. burnetii was heat-sensitive with a D value of 1.75 min. Salmonella Muenchen showed similar UV inactivation kinetics and is, thereby, suggested as a suitable surrogate to C. burnetii for the pilot-scale UV-C processing studies of SM.